Is Direct Method Cash Flow Reporting Better at Predicting Future Performance? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
“Cash is king” goes the saying. Even companies enjoying brisk business have been known to fail because of unhealthy cash flows. The accounting profession is split over the benefits of the direct method (DM) versus the indirect method (IM) of preparing cash flow reports. In a study of over 100 US-based companies which used direct cash flow statements, Singapore Management University accounting professor Yoonseok Zang shows conclusively that the direct method does better at predicting future performance and earnings. --------------------------------------------------------------------------------